Ovariohisterectomia por LESS com dispositivo multiportal artesanal em felinos - Gavioli, Felipe Baldissarella (2018)
The purpose of this study was: (1) to assess the use of a handmade multiport access device for LESS ovariohysterectomy (OVH) in queens. Total surgical time and time to achieve each operative step was compared between modified-LESS and two-port laparoscopic-assisted technique, performed by a non-proficient surgeon; (2) to compare total surgical time, complications and postoperative pain among OVH approaches in cats: LESS using a handmade access device, two-port laparoscopic-assisted and conventional technique using the Snook spay hook. On the first step of the study 16 queens were distributed in two surgery groups: modified-LESS (LESS; n=8) and two-port laparoscopic-assisted approach (TPLA; n=8). Total surgical time and time to achieve surgical steps, as well as technical issues, were compared between groups. On the second stage of the study, 36 queens were distributed in 3 groups: LESS (n=12), TPLA (n=12) and conventional approach (OPEN; n=12). Groups were compared regarding total surgical time, complications and postoperative pain by UNESP-Botucatu’s (EUNESP), feline version of Glasgow’s (EGLASGOW) and dynamic interactive visual analogue (DIVAS) scales. On the first study, access to the abdominal cavity was shorter in LESS than in TPLA (p=0,041). However, total surgical time was not affected (p=0,487). On the second study, TPLA-OVH surgery (23.4±3.1 min; range 18,8-28,0 min) was longer (P<.05) than LESS (19.0±5.6 min; range 13.2-31.0 min) and OPEN (16.9±1.8 min; range 14.5-19.5 min) approaches. No major complication was reported. Postoperative pain was increased in T2 on groups OPEN (DIVAS) e TPLA (DIVAS and EUNESP). LESS-OVH was less painful than TPL-OVH at T2 (EUNESP and DIVAS) and at T4-6 (DIVAS), and OPEN-OVH at T2 (EUNESP and EGLASGOW). In conclusion, LESS-OVH using a homemade access device in cats may be as safe and time consuming as the two-port lap-assisted and open approaches. However, the modified-LESS-OVH yields reduced pain, specially at 2 hours postop.